Effect of the state of the surface layers on the strength of materials for optoelectronic and sensors devices - Maslov, V.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The goal of this work is to determine the correlation of the strength of brittle amorphous nonmetallic materials with the defective surface layers and their physical properties. The defective surface layer of materials for optoelectronic and sensors devices consists of abundant structural near-surface defects, which are displaced under action of constant load and thermal fluctuations, reducing the elasticity of the surface layer. Microcreep processes in tested materials can be described by a general equation that is known as the logarithmic microcreep equation. The applicability of this equation for tested optical materials is indicative of the generality of microcreep processes in crystalline and amorphous hard materials. For each grade of polished optical glass, a minimal residual defective layer exists. The parameters of this layer are interrelated with the mechanical properties of glass, such as microhardness and optical strain coefficient, and thermophysical properties, such as thermal diffusivity, sintering temperature, and annealing temperature. The greater are the values of these properties, the less is the concentration of disrupted interatomic bonds. Based on the test results, the corresponding equation, using the parameter E⋅a¹/², for determining the strength of optical silicate glass and glassceramic has been proposed.